2020
DOI: 10.1111/1365-2435.13577
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of global environmental change drivers on non‐structural carbohydrates in terrestrial plants

Abstract: Non‐structural carbohydrates (NSCs, including soluble sugars and starch) are essential to support the growth and survival of terrestrial plants. Starch and sugars play different roles in multiple plant ecological functions such as drought tolerance, growth and plant defence, and several other processes which are being rapidly shaped by global environmental change. However, it is uncertain whether soluble sugars and starch show different responses across plant functional types, tissue types and treatment condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 84 publications
4
28
0
Order By: Relevance
“…Previous studies have reported that the value of δ 13 C showed a more consistent seasonal signal for climate change across sites than ring width (Maxwell et al, 2020). In addition, non-structural carbohydrate is the most important mobile C pool and the material basis for growth and metabolism in organisms; they mainly include soluble sugar and starch (Du et al, 2020;Herrera-Ramirez et al, 2020). In well-irrigated conditions, Panicum maximum has been reported to maintain stoichiometric homeostasis in a warming climate, and this was related to the distribution of sugars among different organs (Viciedo et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have reported that the value of δ 13 C showed a more consistent seasonal signal for climate change across sites than ring width (Maxwell et al, 2020). In addition, non-structural carbohydrate is the most important mobile C pool and the material basis for growth and metabolism in organisms; they mainly include soluble sugar and starch (Du et al, 2020;Herrera-Ramirez et al, 2020). In well-irrigated conditions, Panicum maximum has been reported to maintain stoichiometric homeostasis in a warming climate, and this was related to the distribution of sugars among different organs (Viciedo et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Though the extent of inter and intraspecific variation in wood C concentrations is now better understood, studies evaluating the adaptive significance of this trait, and many wood chemical traits other than nonstructural carbohydrate concentrations (Du et al, 2020), remain scarce. A handful of studies have explored wood C concentrations in relation to WDan important ecological and life-history trait among trees (Chave et al, 2009;Kraft et al, 2010;D ıaz et al, 2016) with recent meta-analyses indicating a statistically significant, negative wood C concentration-WD relationship across a dataset of 470 angiosperm and conifer species Ó 2021 The Authors New Phytologist Ó 2021 New Phytologist Foundation New Phytologist (2021) 232: 123-133 123 www.newphytologist.com (Martin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The analyses on root traits also have emphasized the important role of mycorrhizal pathways in regulating ecosystem functions under environmental changes (Ma et al., 2018; Soudzilovskaia et al., 2015). Overall, the data mining on species‐level observations has facilitated the process‐understanding of biological responses to global changes, such as plant non‐structural carbohydrates (Adams et al., 2017; Du, Lu, & Xia, 2020), leaf photosynthetic capacity (Kattge, Knorr, Raddatz, & Wirth, 2009) and respiration (Atkin et al., 2015), plant biomass (Xia & Wan, 2008; Xu, Lu, et al, 2019b), and soil microbial community composition (De Vries et al., 2012).…”
Section: General Patterns Of Biological Responses To Global Changes Fmentioning
confidence: 99%